Trilobites of the Holm Dal Formation (late Middle Cambrian), central North Greenland - Robison, Richard A. (Meddelelser om Grønland. Geoscience, 1988)
An unusually diverse trilobite fauna in the Holm Dai Formation is dominated by polymeroid genera and species that are most characteristic of the lower and middle Cedaria Zone as widely applied in North America. Several agnostoid species are characteristic of the upper Lejopyge laevigata Interval-zone of Robison (1984), and correlation with the Swedish standard for north-western Europe indicates a late Middle Cambrian age. Biogeographic analysis shows that continental endemism of the 34 polymeroid genera and 43 polymeroid species in the Holm Dal Formation exceeds 88 and 97percent respectively. In marked contrast, all 12 of the Holm Dal agnostoid genera and at least 13 of the 15 agnostoid species have intercontinental distributions (0 and 13 percent endemism respectively). Comparisons with coeval North American faunas suggest that Middle Cambrian biozones based on polymeroid species may be useful on a regional scale, but probably will not be applicable on a continental scale. Genus-based polymeroid zones may be applicable on a continental scale, but long stratigraphic ranges of genera will limit precision. Species-based agnostoid zones will be applicable globally, but probably will be most useful in deposits representing the neritic to oceanic transition. Fifty-eight trilobite species, some in open nomenclature, are described from Peary Land and Freuchen Land. Of the taxa represented, 9 of 34 genera are new: Balderia, Conopolus, Durinia, Holmdalia, Pearylandia, Tavsenia, Toragnostus, Verditerrina, and Wandelella. Twenty-four species are new: Balderia aspera, Blountia bella, Bolaspidella stymacantha, Cedaria major, Cedaria tumicephala, Conopolus granulus, Crepicephalus eos, Durinia granulosa, Elrathia omega, Glaphyraspis alpha, Madarocephalus scolus, Marjumia brevifrons, Marjumia spinosa, Matania matuta, Matania quadrata, Modocia planata, Nixonella furta, Olenoides ternus, Onchonotopsis physala, Pearylandia parva, Syspacheilus catatate, Tavsenia ditrema, Verditerrina lacinia,and Wandelella compta. In addition, the new species Conopolus rasettii is described from Quebec, Canada. A lectotype is designated for Proagnostus bulbus Butts 1926, the type species of Proagnostus.